The Effects of Supplementation with Omega-3 Polyunsaturated Fatty Acids on Cardiac Rhythm: Anti-Arrhythmic, Pro-Arrhythmic, Both or Neither? It Depends… - Rauch, Bernhard; Senges, Jochen (Frontiers in Physiology, 2012)
Extra supplementation of omega-3 fatty acids (Ω-3) has been associated with a decreased cardiovascular risk, thereby focusing on a potentially preventive effect on tachyarrhythmias and sudden cardiac death. Recent randomized controlled trials, however, challenge the efficiency of the additional application of Ω-3 in its anti-arrhythmic effect under certain clinical conditions. The present paper reflects the results of earlier and recent clinical studies with respect to the individual background conditions that potentially may explain apparently conflicting clinical data. It is suggested that the efficiency of Ω-3 supplementation to prevent cardiac arrhythmias strongly depends on the underlying clinical and pharmacological conditions, a hypothesis that may be supported by the data from experimental animal studies and the molecular interactions of Ω-3 at the cellular level.